The effects of dietary nitrate on plasma glucose and insulin sensitivity in sheep - Villar, Maria Laura; Godwin, Ian R.; Hegarty, Roger S.; Dobos, Robin Christopher; Smith, Katherine A.; Clay, Jonathon W.; Nolan, John V. (Wiley Online Library, 2019)
Nitrate (NO3 ¯) is an effective non‐protein nitrogen source for gut microbes and reduces enteric methane (CH4) production in ruminants. Nitrate is reduced to ammonia by rumen bacteria with nitrite (NO2 ¯) produced as an intermediate. The absorption of NO2 ¯ can cause methaemoglobinaemia in ruminants. Metabolism of NO3 ¯ and NO2 ¯ in blood and animal tissues forms nitric oxide (NO) which has profound physiological effects in ruminants and has been shown to increase glucose uptake and insulin secretion in rodents and humans. We hypothesized that absorption of small quantities of NO2¯ resulting from a low‐risk dose of dietary NO3¯ will increase insulin sensitivity (SI) and glucose uptake in sheep. We evaluated the effect of feeding sheep with a diet supplemented with 18 g NO3 ¯/kg DM or urea (Ur) isonitrogenously to NO3¯, on insulin and glucose dynamics. A glucose tolerance test using an intravenous bolus of 1 ml/kg LW of 24% (w/v) glucose was conducted in twenty sheep, with 10 sheep receiving 1.8% supplementary NO3 ¯ and 10 receiving supplementary urea isonitrogenously to NO3¯. The MINMOD model used plasma glucose and insulin concentrations to estimate basal plasma insulin (Ib) and basal glucose concentration (Gb), insulin sensitivity (SI), glucose effectiveness (SG), acute insulin response (AIRg) and disposition index (DI). Nitrate supplementation had no effect on Ib (p > .05). The decrease in blood glucose occurred at the same rate in both dietary treatments (SG; p = .60), and there was no effect of NO3¯ on either Gb, SI, AIRg or DI. This experiment found that the insulin dynamics assessed using the MINMOD model were not affected by NO3¯ administered to fasted sheep at a low dose of 1.8% NO3¯ in the diet.